2000
DOI: 10.1042/bj3480029
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human hyaluronan synthases in response to external stimuli

Abstract: In the present study we have investigated the expression of mRNAs for hyaluronan synthase isoforms (HAS1, HAS2 and HAS3) in different cells in response to various stimuli. Human mesothelial cells, which synthesize large amounts of hyaluronan, express mRNAs encoding all three HAS isoforms, whereas their transformed counterparts, mesothelioma cells, which produce only minute amounts of hyaluronan, express only HAS3 mRNA. Human lung fibroblasts and the glioma cell line U-118 MG express only the HAS2 and HAS3 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(47 citation statements)
references
References 29 publications
1
43
1
2
Order By: Relevance
“…For example, HA greater than 600 kDA has significant anti‐inflammatory effects on FLS and OA chondrocytes; meanwhile HA of 1.6 MDa or greater promotes Collagen II production in chondrocytes (Bauer et al, ; Wang, Lin, Chiang, Lin, & Hou, ). HA oligomer fragments, however, are both products and activators of proinflammatory mediators in joint pathologies (P. Ghosh, ; S. Ghosh et al, ; Itano et al, ; Jacobson, Brinck, Briskin, Spicer, & Heldin, ). We confirmed that HA greater than 3 MDa is best produced when IL‐1β, TNF‐α, and TGF‐β1 are all supplemented (Blewis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HA greater than 600 kDA has significant anti‐inflammatory effects on FLS and OA chondrocytes; meanwhile HA of 1.6 MDa or greater promotes Collagen II production in chondrocytes (Bauer et al, ; Wang, Lin, Chiang, Lin, & Hou, ). HA oligomer fragments, however, are both products and activators of proinflammatory mediators in joint pathologies (P. Ghosh, ; S. Ghosh et al, ; Itano et al, ; Jacobson, Brinck, Briskin, Spicer, & Heldin, ). We confirmed that HA greater than 3 MDa is best produced when IL‐1β, TNF‐α, and TGF‐β1 are all supplemented (Blewis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronan is an important constituent of the extracellular matrix. PDGF-BB-stimulated normal human mesothelial cells express both hyaluronan synthase and hyaluronan [115][116] .…”
Section: Pathway Regulationmentioning
confidence: 99%
“…HA biosynthesis can be stimulated by many growth factors and cytokines. In the vast majority of cases, transcriptional upregulation of HAS2 appears to be the preferred mechanism for stimulation of HA biosynthesis (Jacobsen et al, 1999; Kaback and Smith, 1999; Elvin et al, 1999; Nishida et al, 2000; Karvinen et al, 2003; Pasonen‐Seppanen et al, 2003; Tanimoto et al, 2001). HAS2 expression is upregulated by the transforming growth factor‐beta (TGF‐β)/bone morphogenetic protein (BMP) superfamily members, interleukin‐1 beta (IL‐1β), tumor necrosis factor‐alpha (TNF‐α), epidermal growth factor (EGF), keratinocyte growth factor (KGF), and many other factors.…”
Section: Biosynthesismentioning
confidence: 99%
“…HAS2 expression is upregulated by the transforming growth factor‐beta (TGF‐β)/bone morphogenetic protein (BMP) superfamily members, interleukin‐1 beta (IL‐1β), tumor necrosis factor‐alpha (TNF‐α), epidermal growth factor (EGF), keratinocyte growth factor (KGF), and many other factors. HAS2 is potently inhibited by glucocorticoids, through a combination of transcriptional repression and increased mRNA turnover (Jacobsen et al, 1999; Zhang et al, 2000). HAS2 is the key enzyme in several adult tissues, such as the dermis and the ovaries (Fulop et al, 1997; Sugiyama et al, 1998).…”
Section: Biosynthesismentioning
confidence: 99%